Utilization of Ferrate Ion (FeO42-) as Oxidizing Agent for Reducing Color Intensity of Peat Water - Retno Agnestisia; Karelius Karelius; Rendy Muhamad Iqbal; Dyah Ayu Pramoda Wardani; Midun Efendi Patar Sihombing; Sri Yulandari Simangunsong; Junita Dongoran (Program Studi Kimia, Universitas Lambung Mangkurat, 2023)
Peat water from Central Kalimantan is generally yellow to brownish-red in color. It causes peat water to not be used as a source of water for daily needs. Humic acid, fulvic acid, and humin are organic compounds that cause peat water to become colored. One alternative step that can be taken for reducing the color intensity of peat water is to degrade color-causing organic compounds by using an oxidizing agent. A hexavalent form of iron ion (Fe6+), commonly called ferrate (FeO42-) in potassium ferrate compound, is a powerful oxidizing agent used in the present study. Potassium ferrate (K2FeO4) was synthesized by a wet oxidation method and characterized using a UV-Vis spectrophotometer and an X-Ray Diffractometer (XRD). The ferrate solution is purplish-red in color with a maximum wavelength of 510 nm. The XRD pattern shows strong diffraction peaks at 2θ which are characteristic of K2FeO4. The ferrate solution was then used to degrade color-causing organic compounds in the peat water from Central Kalimantan. Determination of the optimum degradation conditions was monitored by the absorbance decrease of organic compounds in peat water at a wavelength of 370 nm. The results showed that ferrate solution with a concentration of 80 ppm was able to degrade organic compounds in peat water at pH 8, with a removal efficiency of 100%. Keywords: oxidizing agent, ferrate ion (FeO42-), peat water